The Economic Impact of International Tourism on the Indonesian Economy - Adi Lumaksono; D.S. Priyarsono; Kuntjoro .; Rusman Heriawan (Forum Pasca Sarjana, 2012)
Tourism has played an important role in the Indonesian economy especially inbound tourists which give foreign exchange earnings. On the other hand, outbound tourists bring dollars outside Indonesia. It will have an impact on tourism balance which is still surplus in the case of Indonesia. This study finds that the surplus of tourism balance tends to decrease. By using econometric models, this study also identifies the variables which influence inbound and outbound tourists both the number of arrival/departure and their average expenditure per visit. GDP was the most influencing variable. Simulation will be applied to identify the impacts of policy on the flow of foreign exchange through international tourism. The results of this simulation will be used to analyze the economic impact of inbound tourists by using Input-Output Model. It shows that exchange rate will give higher impact compared to the other variables. Key words: inbound-outbound tourist, tourism balance, economic impact, econometric model, input-output analysis